Decision Support System for Submitting Credit using Analytical Hierarchy Process (AHP) Method Based on Android on Save and Loan Cooperatives Cubg Pasar Kemis Tangerang - Nitema Gulo; Euis Nurninawati; R. Achmad Rachmat S; Dedy Prasetya Kristiadi (IJISTECH (International Journal of Information System and Technology), 2022)
The government provides credit assistance to the community in order to increase income through small and medium enterprises (micro) through cooperatives. The limited funds provided and the large number of creditors require the use of a good and appropriate decision support system. Supporters of credit decisions used in savings and loan cooperatives in Tangerang have not used an accurate method of selecting prospective creditors. Therefore, a faster, more precise and accurate decision-making method is needed. The Analytical Hierarchy Process (AHP) method is a method that uses hierarchical process considerations to calculate the weights on each criterion such as economic conditions, character, capital, capacity, collateral by comparing sub-criteria in determining creditworthiness. This study uses the method of observation, interviews and literature study. Meanwhile, data analysis uses SWOT, system tools use Unified Modeling Language (UML). The results of this study will provide recommendations in the form of a decision-making system that is accurate, fast and easy. The application will be built with Android to support user convenience and speed up transactions.